An electroactive versatile matrix for the construction of sensors - Cortez, María Lorena (2011)
The strong interaction between a positively charged electroactive polyelectrolyte (polyallylamine derivatized with an osmium complex) with an anionic surfactant (sodium dodecyl sulfate) produces a composite material soluble in organic solvents. The organic solution of this material can be applied on electrode surfaces (gold, graphite), generating a very stable modified electrode. The modified electrode presents a very efficient charge propagation through the film and it can be used in further modifications. As an example glucose oxidase is adsorbed; in presence of glucose, this electrode presents catalytic currents with similar values compared to others built by self-assembling operations. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.